Outcome-based reimbursement in Central-Eastern Europe and Middle-East - Ádám, Ildikó; Callenbach, Marcelien; Németh, Bertalan; Vreman, Rick A.; Tollin, Cecilia; Pontén, Johan; Dawoud, Dalia; Elvidge, Jamie; Crabb, Nick; van Waalwijk van Doorn-Khosrovani, Sahar Barjesteh; Pisters-van Roy, Anke; Vincziczki, Áron; et al. (Frontiers in Medicine, 2022)
Outcome-based reimbursement models can effectively reduce the financial risk to health care payers in cases when there is important uncertainty or heterogeneity regarding the clinical value of health technologies. Still, health care payers in lower income countries rely mainly on financial based agreements to manage uncertainties associated with new therapies. We performed a survey, an exploratory literature review and an iterative brainstorming in parallel about potential barriers and solutions to outcome-based agreements in Central and Eastern Europe (CEE) and in the Middle East (ME). A draft list of recommendations deriving from these steps was validated in a follow-up workshop with payer experts from these regions. 20 different barriers were identified in 5 groups, including transaction costs and administrative burden, measurement issues, information technology and data infrastructure, governance, and perverse policy outcomes. Though implementing outcome-based reimbursement models is challenging, especially in lower income countries, those challenges can be mitigated by conducting pilot agreements and preparing for predictable barriers. Our guidance paper provides an initial step in this process. The generalisability of our recommendations can be improved by monitoring experiences from pilot reimbursement models in CEE and ME countries and continuing the multistakeholder dialogue at national levels.